Surface treatment on polymethylmethacrylate hybrid using argon flouride excimer laser - Bidin, Noriah; Zarzali Shah, Aishah; Mat Daud, Yaacob (Faculty of Science, 2008)

(untitled)
Flatness and smoothness of optical components are crucial to maintain the uniformity of light distribution. However, to treat a very delicate surface require, a controllable and gentle technique. This can be achieved by using ultraviolet laser as a micromaching. In this case, an argon fluoride excimer laser was employed as a source of ablation. Polymethylmethacrylate (PMMA) film is coated on a Perspex substrate. Fabry-Perot interferometer was incorporated as a dynamic transducer to monitor the surface treatment. The Hybrid plastic-polymer was then ablated by series pulses of UV excimer laser. The pulses are controlled until the appearance of straight and equidistance line fringes. The degree of flatness achieved by using this laser surface treatment is ?/10.